Improved Performance of VOx‐Coated Li‐Rich NMC Electrodes. Issue 11 (27th July 2015) - Laszczynski, Nina; von Zamory, Jan; Kalhoff, Julian; Loeffler, Nicholas; Chakravadhanula, Venkata Sai Kiran; Passerini, Stefano
Abstract: A VO x coating of Li1.2 Mn0.56 Ni0.16 Co0.08 O2, made through a low‐temperature annealing process (350 °C), results in the formation of a protecting layer, which enables electrodes to be prepared with an aqueous binder, offering a significantly improved electrochemical performance. The comparison with uncoated electrodes demonstrates the significantly improved performance of VO x ‐coated Li1.2 Mn0.56 Ni0.16 Co0.08 O2, which substantially outperforms the uncoated material by 30 mAh g −1 at moderate rates. The VO x coating is found to prevent the contact of Li1.2 Mn0.56 Ni0.16 Co0.08 O2 with water from the aqueous‐binder processing, preventing leaching of metal cations. Upon cell operation, the coating delays the transformation of the active layer material into the spinel phase, occurring at low voltages, thus delaying its typical capacity fade upon cycling. Finally, the coating contributes to the overall material capacity, while ensuring the lithium deintercalation and intercalation processes. Abstract : Delay tactics : A VO x coating on the high‐voltage cathode material Li1.2 Mn0.56 Ni0.16 Co0.08 O2 enables the use of environmentally friendly aqueous binders and grants improved capacities upon cycling, while significantly delaying the irreversible transformation of the active material into the spinel‐phase Li‐rich NMC.